Urgensi Pemenuhan Hak Anak Berkebutuhan Khusus (Penyandang Disabilitas) Dalam Bidang Kesehatan - Fransiska Novita Eleanora; Nursolihi Insani (Direktorat Penelitian dan Pengabdian (DPPM) Universitas Pelita Bangsa, 2022)
The fulfillment and protection of the rights of every citizen is the responsibility of the Government in fulfilling them, including the rights of children with disabilities to their rights. Children's rights are the same as other children and most importantly the right to education and health in terms of protection and gender equality. Protection and fulfillment of their rights in the health sector, efforts to maintain children's health are carried out from in the womb, as well as toddlers, to adolescents, including efforts to maintain the health of disabled children and children who need protection from physical, psychological and sexual violence with medical rehabilitation and treatment. adequate, so that in good health, children can enjoy their rights properly. because in a healthy body there is a healthy soul, a healthy child will also focus and concentrate on exercising his rights as a manifestation of the protection of children's human rights through services to children and the provision of medicine for healing. Therefore, this study will discuss the urgency of fulfilling and protecting the rights of children with disabilities in the health sector